Anorexia and use of social networks in adolescent - Lucciarini, Florencia (2021)
The aim of this theoretical article was analyze the possible relationship between the use of social networks and the development of anorexia in adolescents from 10 to 19 years old through a systemic and cognitive-behavioral approach. The concept of Anorexia Nervosa (AN), which is included within the eating disorders (ED), was described and the social networks most usedby this age range were studied. It is concluded about the significant relationship between the development of AN, and the use of social networks. The body changes in adolescents, as the needfor approval of their identity by their environment, place them in a situation of vulnerability. Although the social networks can be a factor for a positive validation, they could constitute a riskfactor that triggers an ED, particularly AN, in adolescents.